EL PAPEL DEL INGLÉS EN EL FOMENTO DEL MULTILINGÜISMO EN LA UNIVERSIDAD - Lasagabaster, David (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract After decades of neglect, Spanish universities have only lately placed internationalisation high on the agenda. The internationalisation process is inextricably linked to the need to foster multilingualism and, above all, to improve Spanish university students’ language competence in English. But in bilingual universities such as the University of the Basque Country (UPV/EHU), the increasing presence of English entails the need to find a balance between the languages of communication (foreign languages) and the languages of identification (vernacular languages: Basque and Spanish). However, the number of studies on the impact of internationalisation and multilingual policies on the university community is scant, which is why the present article aims to examine students’ and teaching staff’s perceptions of the challenge represented by the spread of multilingualism in higher education. The participants in the study were 495 local undergraduates and 103 teachers, making a total of 598 university members. They were invited to fill out a questionnaire which included ítems related to three main issues: internationalisation, academic mobility and multilingualism. The statistical analyses reveal linguistic strains between the languages in contact and, especially, in issues concerning the presence of English. The article finally attempts to draw out implications for language teaching and language policy at university. Resumen En la actualidad las universidades españolas han colocado entre sus prioridades la internacionalización tras décadas en las que no se le prestó demasiada importancia. El proceso de internacionalización está indefectiblemente unido a la necesidad de fomentar el multilingüismo y, especialmente, la competencia lingüística en inglés del alumnado universitario español. Pero en universidades bilingües como la Universidad del País Vasco (UPV/EHU), la creciente presencia del inglés supone la necesidad de buscar un equilibrio entre las lenguas de comunicación (las lenguas extranjeras) y las lenguas de identificación (las lenguas propias, euskera y castellano). Sin embargo, existe poca investigación sobre el efecto de la internacionalización y el multilingüismo en los diferentes sectores que constituyen la comunidad universitaria, por lo que en este estudio se examinan las percepciones que tanto el profesorado como el alumnado muestran hacia el reto que supone el multilingüismo en la educación terciaria. En esta investigación participaron 598 miembros de la comunidad universitaria, divididos en 495 estudiantes de grado y 103 profesores. Estos sujetos fueron invitados a responder un cuestionario que versaba sobre diversas cuestiones divididas en tres grandes grupos: internacionalización, movilidad académica y multilingüismo. Los análisis estadísticos revelan la existencia de tensiones lingüísticas entre las distintas lenguas en contacto y, especialmente, en el caso de las cuestiones que tienen que ver con la presencia del inglés. Los resultados sugieren asimismo una serie de implicaciones relacionadas con la enseñanza de lenguas y la política lingüística universitaria.